The affair [compact disc, unabridged] : a novel - Steel, Danielle (Recorded Books, Llc, 2021)
A fashion magazine executive navigates a scandal involving her son-in-law's affair with a Hollywood actress, while her daughters support each other through infidelity, commitment issues and personal secrets.